Ceratodus tunuensis, sp. nov., a new lungfish (Sarcopterygii, Dipnoi) from the Upper Triassic of central East Greenland - Agnolin, Federico; Mateus, Octávio; Milàn, Jesper; Marzola, Marco; Wings, Oliver; Adolfssen, Jan Schulz; Clemmensen, Lars B. (Journal of Vertebrate Paleontology)
The fossil record of post-Paleozoic lungfishes in Greenland is currently restricted to a few brief reports of isolated and undetermined tooth plates coming from the uppermost Fleming Fjord Formation (late Norian) in Jameson Land, central East Greenland. Here, we describe Ceratodus tunuensis, sp. nov., a new dipnoan from a thin bed of calcareous lake mudstone from the Ørsted Dal Member of the Fleming Fjord Formation. The Ceratodus fossil record indicates that during the Late Triassic, this genus was restricted to the middle latitudes of the Northern Hemisphere. This record matches previous paleobiogeographical analyses and indicates that terrestrial biota during the Late Triassic was strongly influenced by paleolatitude. Fil: Agnolin, Federico. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina. Fundación de Historia Natural Félix de Azara; Argentina Fil: Mateus, Octávio. Universidade Nova de Lisboa; Portugal Fil: Milàn, Jesper. Universidad de Copenhagen; Dinamarca Fil: Marzola, Marco. Universidade Nova de Lisboa; Portugal. Universidad de Copenhagen; Dinamarca Fil: Wings, Oliver. Universidad de Halle-Wittenberg; Alemania Fil: Adolfssen, Jan Schulz. Ministry of Mineral Resources; Groenlandia Fil: Clemmensen, Lars B. Universidad de Copenhagen; Dinamarca